"The light at the end of the tunnel". Discharge experience of older patients with chronic diseases: A multi‐centre qualitative study. (16th February 2021) - Facchinetti, Gabriella; Albanesi, Beatrice; Piredda, Michela; Marchetti, Anna; Ausili, Davide; Ianni, Andrea; Di Mauro, Stefania; De Marinis, Maria Grazia
Abstract: Aim: To explore the experiences of being discharged from hospital of older patients with chronic diseases at time of discharge. Design: Multi‐centre descriptive qualitative study. Methods: Semi‐structured interviews were conducted with older patients with chronic diseases discharged from two Italian university hospitals, between March 2017 and October 2019. The interviews were audio‐recorded, transcribed verbatim and analysed using inductive content analysis. Several strategies were used to ensure the credibility, dependability, confirmability, authenticity and transferability of the findings. The study was reported in accordance with Standards for Reporting Qualitative Research and Consolidated criteria for reporting qualitative research. Results: Sixty‐five patients participated in the study. Six main categories emerged: feelings, need for information, time of fragility, need for support, need for trusting relationships, and home as a caring place. Conclusion: Older patients with chronic diseases are patients who require quality discharge planning with a patient‐centred care vision. Healthcare professionals should intervene more extensively and deeply in the discharge process, balancing the patients' perception of their needs against organizational priorities and the wish to return home with that of not being abandoned. Impact: Discharge from hospital remains an area of concern as older people have varying degrees of met and unmet needs during and following hospital discharge. Discharge is characterized by conflicting feelings of patients, who need information and support of healthcare professionals through trusting and continuous relationships. Understanding the experience of discharge is essential to support older patients with chronic diseases, considering that discharge from hospital is not an end point of care but a stage of the process involving care transition. The reframing of discharge as another transition point is crucial for healthcare professionals, who will be responsible for making their patients fit for discharge by preparing them to manage their chronic condition at home.